Perioperative Multi-Kingdom Gut Microbiota Alters in Coronary Artery Bypass Grafting - Zhou Fu; Yanxiong Jia; Jing Zhao; Yulin Guo; Boqia Xie; Kun An; Wen Yuan; Yihang Chen; Jiuchang Zhong; Zhaohui Tong; Xiaoyan Liu; Pixiong Su (Biomedicines, 2025)
Background: Coronary artery bypass grafting (CABG) is one of the main treatments for coronary heart disease (CHD). Gut microbiota, including bacteria, fungi, archaea, and virus, has been reported to be associated with CHD. However, the changes in the multi-kingdom gut microbiota after CABG are not yet clear. This study aimed to explore the changes in multi-kingdom gut microbiota during the early postoperative period of CABG. Methods: We collected fecal samples from 40 patients before and 1 week after CABG surgery. Metagenomic sequencing was used to detect the microbial spectrum and gene functions in the patients’ fecal samples. Results: Post-CABG patients exhibited significant changes in the composition of multi-kingdom gut microbiota and gene functions. Among bacteria, beneficial species such as Bifidobacterium, Bacteroides, and Blautia were significantly reduced after CABG, while the harmful species Enterococcus was significantly increased. In fungi, Schizosaccharomyces pombe was significantly decreased in the postoperative group, while Saccharomyces cerevisiae and Aspergillus chevalieri were significantly increased postoperatively. Spearman correlation analysis indicated that Schizosaccharomyces pombe had positive interactions with beneficial bacteria such as Lachnospiraceae, Ruminococcus, and Blautia. Among archaea, the preoperatively enriched Methanomethylovorans-SGB40959 was significantly reduced postoperatively, and Spearman correlation analysis showed a significant positive interaction with probiotics Ruminococcus and Dorea. In viruses, the phage Enterococcus virus EFP01, which infects Enterococcus, was significantly increased postoperatively and showed a significant positive interaction with Enterococcus. Additionally, postoperative dysregulation of gene functions such as the Phosphoenolpyruvate-dependent Sugar Phosphotransferase System (PTS), Transposition, DNA-mediated, and Transposase Activity was observed, and Spearman correlation analysis indicated significant correlations between the dysregulated gene functions and the microbial communities. Conclusions: This study comprehensively revealed the changes in multi-kingdom species post-CABG. The reduction of beneficial microorganisms and the increase of harmful microorganisms after surgery are of significant clinical importance for understanding the overall health status of post-CABG patients and for optimizing postoperative treatment plans. Future research needs to further explore how to improve the prognosis of post-CABG patients by modulating the gut microbiota.